Successful endoscopic closure of an esophageal leak after endoscopic ultrasound-guided hepaticoesophagostomy by using n-butyl-2 cyanoacrylate - Renma Ito; Yusuke Hashimoto; Masafumi Ikeda (International Journal of Gastrointestinal Intervention, 2019)
Endoscopic ultrasound-guided hepaticoesophagostomy (EUS-HES) refers to EUS-guided biliary access from the abdominal part of the esophagus, an uncommon choice of route for biliary drainage. In the patient reported herein, an esophageal laceration and leakage at the site of placement of a metal stent occurred a few days after EUS-HES. To plug the laceration, 0.5 mL of n-butyl-2 cyanoacrylate mixed with 1 mL of lipiodol was injected through an endoscopic retrograde cholangiopancreatography catheter. We performed EUS-guided transgastric drainage for drainage of the peritoneal fluid collection. The procedures were successful and the laceration eventually healed, with no further leakage.